Proceso atención de enfermería en paciente femenina de 25 años de edad con desgarro perianal grado 1. - Hidalgo Salazar, Ginger Jeanela (2022)
The present research is about a 25-year-old female patient with a grade 1 perianal tear, whose objective was to elaborate a nursing care process for a 25-year-old female patient with a grade I perineal tear. Grade I perineal trauma is a vaginal tear of lesser severity that only involves the perineum, that is, the skin between the vaginal opening and the rectum and the tissue that will be found directly under the skin. Perineal tears have been found to be a consequence of the age of the patients. The immaturity of the young patients generates complications due to the narrowness of the soft canal. It is concluded that the nursing interventions and also the medical treatment became of vital importance for the patient, thus improving her state of health in a satisfactory way.